Comparison of Closure versus Non-closure of Buccal Mucosal Graft Harvesting Site in Urethroplasty. - Arsalan Shezad; Tanzeel Gazder; Syed Rabiullah; Mazahir Zulfiqar; Usman Qamar; Haris Jameel; Saeed Abidi; Manzoor Hussain (International Journal of Endorsing Health Science Research, 2023)
Background: Buccal mucosal graft is commonly used in substitution urethroplasty for the treatment of anterior urethral strictures. However, the optimal management of the donor site remains a topic of debate. This prospective study aimed to compare the outcomes and morbidity associated with closure versus non-closure of the buccal mucosal graft harvesting site in urethroplasty. Methodology: A total of 60 patients with anterior urethral strictures underwent buccal mucosal urethroplasty. The patients were divided into two groups: group A (non-closure, n=30) and group B (closure, n=30). Post-operative pain, perioral numbness, early return to diet, and swelling of the cheek were assessed and compared between the two groups. Pain was measured using the Visual Analog Scale (VAS), and statistical analysis was performed using appropriate tests. Results: The mean age of the patients was 35.73 ± 13.42 years, and the mean length of the stricture was 58.45 ± 26.87 mm. Post-operative pain scores measured through VAS were comparable between the closure and non-closure groups at different time points. Perioral numbness was observed in 43.33% of the non-closure group and 30.0% of the closure group (p=0.284). Early return to diet was reported in 40.0% of the non-closure group and 70.0% of the closure group (p=0.019). Swelling of the cheek was noted in 53.33% of the non-closure group and 33.33% of the closure group (p=0.118). Conclusion: This study suggests that non-closure of the buccal mucosal graft harvesting site in urethroplasty results in less post-operative pain, early return to diet, and lower perioral numbness. However, it is associated with increased swelling of the cheek. These findings support the use of non-closure as a viable alternative to closure of the buccal mucosal graft harvesting site. Further research with larger sample sizes and longer-term follow-up is warranted to validate these findings and assess additional outcomes such as stricture recurrence and cosmetic outcomes.